2009
DOI: 10.3766/jaaa.20.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Survey of College Students on iPod Use and Hearing Health

Abstract: Most of these college students should not be at great risk of hearing loss from their iPods when used conscientiously. Some concern is warranted for a small segment of these students who seemed to be most at risk because they listened to their iPods at high volume levels for long durations using earbuds, and reported that they may already have hearing loss due to their iPods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 17 publications
9
70
2
3
Order By: Relevance
“…Listeners using ear bud earphones are more at risk, because they fail to Fig. 3 Preferred level of loudness of headphones/ earphones (n = 917) attenuate high ambient noise levels and necessitate increasing volume for acoustic enjoyment [8]. Ear phones are the more common modality used by music listeners [9], as is also found in our study (86.5 %, n = 874), thus putting them in the higher risk group.…”
Section: Discussionsupporting
confidence: 52%
“…Listeners using ear bud earphones are more at risk, because they fail to Fig. 3 Preferred level of loudness of headphones/ earphones (n = 917) attenuate high ambient noise levels and necessitate increasing volume for acoustic enjoyment [8]. Ear phones are the more common modality used by music listeners [9], as is also found in our study (86.5 %, n = 874), thus putting them in the higher risk group.…”
Section: Discussionsupporting
confidence: 52%
“…A different study 37 reported that those who use listen to music at high volumes while wearing headphones had alterations in attention and concentration, as well as another little-known problem -the formation of dermatitis and eczema on the ears. The researchers advised constant care, not only related to volume levels, but also the cleaning of the earphones.…”
Section: Faria and Mellomentioning
confidence: 99%
“…However, youths do not seem to be worried about the harmful effects of intense sounds. It becomes clear when it is considered their attitudes in varied situations of sound exposure 9,10 , thus, it is important to perform researches about teenagers personal stereo users 11,12 . A symptom which is associated with improper sound exposure is tinnitus 3 .…”
Section: Introductionmentioning
confidence: 99%